Identification of TIMP1-induced dysregulation of epithelial-mesenchymal transition as a key pathway in inflammatory bowel disease and small intestinal neuroendocrine tumors shared pathogenesis - Tran, Minh Tuan (Frontiers in Genetics, 2024)
Inflammatory Bowel Disease (IBD) is believed to be a risk factor for Small Intestinal Neuroendocrine Tumors (SI-NET) development; however, the molecular relationship between IBD and SI-NET has yet to be elucidated. In this study, we use a systems biology approach to uncover such relationships. We identified a more similar transcriptomic-wide expression pattern between Crohn’s Disease (CD) and SI-NET whereas a higher proportion of overlapping dysregulated genes between Ulcerative Colitis (UC) and SI-NET. Enrichment analysis indicates that extracellular matrix remodeling, particularly in epithelial-mesenchymal transition and intestinal fibrosis mediated by TIMP1, is the most significantly dysregulated pathway among upregulated genes shared between both IBD subtypes and SI-NET. However, this remodeling occurs through distinct regulatory molecular mechanisms unique to each IBD subtype. Specifically, myofibroblast activation in CD and SI-NET is mediated through IL-6 and ciliary-dependent signaling pathways. Contrarily, in UC and SI-NET, this phenomenon is mainly regulated through immune cells like macrophages and the NCAM signaling pathway, a potential gut-brain axis in the context of these two diseases. In both IBD and SI-NET, intestinal fibrosis resulted in significant metabolic reprogramming of fatty acid and glucose to an inflammatory- and cancer-inducing state. This altered metabolic state, revealed through enrichment analysis of downregulated genes, showed dysfunctions in oxidative phosphorylation, gluconeogenesis, and glycogenesis, indicating a shift towards glycolysis. Also known as the Warburg effect, this glycolytic switch, in return, exacerbates fibrosis. Corresponding to enrichment analysis results, network construction and subsequent topological analysis pinpointed 7 protein complexes, 17 hub genes, 11 microRNA, and 1 transcription factor related to extracellular matrix accumulation and metabolic reprogramming that are candidate biomarkers in both IBD and SI-NET. Together, these biological pathways and candidate biomarkers may serve as potential therapeutic targets for these diseases.